2016
DOI: 10.1016/j.cmet.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Oxidation Is Indispensable for Survival of Human Pluripotent Stem Cells

Abstract: Human pluripotent stem cells (hPSCs) are uniquely dependent on aerobic glycolysis to generate ATP. However, the importance of oxidative phosphorylation (OXPHOS) has not been elucidated. Detailed amino acid profiling has revealed that glutamine is indispensable for the survival of hPSCs. Under glucose- and glutamine-depleted conditions, hPSCs quickly died due to the loss of ATP. Metabolome analyses showed that hPSCs oxidized pyruvate poorly and that glutamine was the main energy source for OXPHOS. hPSCs were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
188
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(195 citation statements)
references
References 33 publications
6
188
1
Order By: Relevance
“…In primed human PSCs, metabolism typically proceeds via the glycolytic pathway, which rapidly switches to oxidative phosphorylation upon differentiation (Zhou et al, 2012;Moussaieff et al, 2015). Compared with differentiated cells, which utilise oxidative phosphorylation as the primary metabolic pathway, these PSCs possess largely underdeveloped and immature mitochondria that are few in number, thus maintaining high rates of glycolysis even under aerobic culture conditions, although a recent report found that these cells can nonetheless utilise oxidative phosphorylation for energy generation through glutamine metabolism (Prigione et al, 2010;Varum et al, 2011;Tohyama et al, 2016). This preference for glycolytic metabolism is reminiscent of the Warburg effect in many highly proliferative cancer cells, typified by an increased conversion of pyruvate to lactate.…”
Section: The Function Of Pi3k/akt/mtor In Regulating Glycolytic Metabmentioning
confidence: 99%
“…In primed human PSCs, metabolism typically proceeds via the glycolytic pathway, which rapidly switches to oxidative phosphorylation upon differentiation (Zhou et al, 2012;Moussaieff et al, 2015). Compared with differentiated cells, which utilise oxidative phosphorylation as the primary metabolic pathway, these PSCs possess largely underdeveloped and immature mitochondria that are few in number, thus maintaining high rates of glycolysis even under aerobic culture conditions, although a recent report found that these cells can nonetheless utilise oxidative phosphorylation for energy generation through glutamine metabolism (Prigione et al, 2010;Varum et al, 2011;Tohyama et al, 2016). This preference for glycolytic metabolism is reminiscent of the Warburg effect in many highly proliferative cancer cells, typified by an increased conversion of pyruvate to lactate.…”
Section: The Function Of Pi3k/akt/mtor In Regulating Glycolytic Metabmentioning
confidence: 99%
“…As noted earlier, stem cells rely heavily on glycolysis, with high expression of hexokinase II, and use fatty acids and glutamine as the main energy source for OxPhos [169,176]. Similarly, cancer cells take up glucose and glutamine at high rates and convert glucose to lactate through aerobic glycolysis in the presence of oxygen ("Warburg effect"), with high expression of hexokinase II [177].…”
Section: Embryo-fetal Characteristics Of Cancermentioning
confidence: 99%
“…Consequently, UCP2 is deeply involved in the regulation of energy metabolism, proliferation and differentiation of hPSCs. It is well established that stem cells heavily rely on glycolysis and use FFA and glutamine as the main energy source for OxPhos [165,169,170]. In stem cells, UCP2 inactivates the pyruvate dehydrogenase complex, thereby shunting substrates such as pyruvate away from glucose oxidation while promoting glycolysis, mediated by expression of high levels of hexokinase II [167,170], and promotes oxidation of alternative substrates such as glutamine and free fatty acids (FFA) [165,170].…”
Section: Stem Cell Metabolism and The Role Of Ucp2mentioning
confidence: 99%
“…To overcome this, new purification methods utilizing the unique metabolic properties of PSCs and CMs have been developed. 73, 74 When PSC-derived cells were cultured with glucose-depleted culture medium containing abundant lactate, only PSC-CMs survived and CM purity was almost 99%. 73 Recently, this method was models, have suggested the effectiveness of PSC-based therapy.…”
Section: Tumor Formationmentioning
confidence: 99%